2021
DOI: 10.3389/fvets.2021.653152
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Feeding Omega-3 Polyunsaturated Fatty Acids to Broiler Breeders on Indices of Immunocompetence, Gastrointestinal, and Skeletal Development in Broiler Chickens

Abstract: Modern broiler chickens are associated with rapid growth rates and superior feed efficiency. However, they are also susceptible to physiological and metabolic disorders (e.g., skin lesions, lameness, sudden death, enteric diseases, myopathies) that exert substantial economic losses to producers. This is further exacerbated by consumer pressure and mandated cessation of production practices such as indiscriminate use of antimicrobial growth promoters. Manipulation of broiler breeder (BB) nutrition and managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 102 publications
0
26
0
Order By: Relevance
“…Fatty acids are essential for embryonic development, bird growth, the development of the central nervous system and the immune system (Noble et al, 1984;Ding and Lilburn, 1996;Wang et al, 2004;Cherian, 2015;Koppenol et al, 2015;Thanabalan and Kiarie, 2021). The balance of fatty acids (FA) can be modulated via the hen's diet.…”
Section: Nutritional Programming Strategiesmentioning
confidence: 99%
“…Fatty acids are essential for embryonic development, bird growth, the development of the central nervous system and the immune system (Noble et al, 1984;Ding and Lilburn, 1996;Wang et al, 2004;Cherian, 2015;Koppenol et al, 2015;Thanabalan and Kiarie, 2021). The balance of fatty acids (FA) can be modulated via the hen's diet.…”
Section: Nutritional Programming Strategiesmentioning
confidence: 99%
“…Besides, dietary fish oil supplementation could increase calcium absorption in the small intestine and improve bone mineralization and quality in laying hens [ 15 , 96 , 97 ]. In addition, fish oil enriched diet also improves reproductive performance, organs functionality, immunocompetence, skeletal health, and gastrointestinal development in breeder hens [ 14 , 16 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary lipids play an important role in the development and remodeling of long bones in broiler chicks [12,13]. Several studies have suggested the positive effects of dietary fish oil on bone health in the broiler production [14][15][16]. Bone content of EPA and DHA, which can be enriched by the diet, has been shown to correlate directly with bone mineral content, bone density, and resistance to force in rat [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, supplementation at a certain level result in achieving therapeutic effects. The ω-3 PUFA-enriched diet in livestock and poultry was shown to modulate the immune system, improve intestinal morphology, fertility, stress resistance, and performance [ 26 29 ].…”
Section: Immunomodulatory Nutrients For Intestinal Healthmentioning
confidence: 99%